An Overview of The Risk Factors for Patients with Inguinal Hernia at Aloei Saboe Hospital in Gorontalo - Potutu, Aliffa Cahya; Abdul, Romy; Kasim, Vivien Novarina A.; Pateda, Sri Manovita; Daud, Serly (Universitas Negeri Gorontalo, 2024)
Introduction: Hernias happen when an organ or tissue bulges through a weak point in the abdominal wall. Inguinal hernias are common and may need surgery. The present study report the overview of the risk to affect the inguinal hernia at Aloei Saboe Hospital.Method: The research focused on patients with inguinal hernias who underwent examinations at Aloei Saboe Hospital, in Gorontalo Province from January to December 2022. The study used the total sampling technique, with a sample size of 42 individuals. It was conducted in September and October 2023 at the same hospital.Results: The data indicates that a significant portion of patients in the range of age 56-65 years (28.6%), with a majority being male (85.7%). Additionally, the majority of patients who were not employed (19.0%) were also found to have this condition, as well as a vast majority of those with a primary diagnosis of inguinal hernia (88.1%).Conclusion: Most patients with inguinal hernia at Aloei Saboe Hospital are males in the late elderly age group who are no longer working. The main diagnosis for most patients is inguinal hernia. The study's findings suggest that the hospital can enhance its system, particularly in archiving medical records or electronic medical forms, to serve its patients better. Key words: Gorontalo, hernias, inguinal hernia